Inter‐Arm Blood Pressure Difference in Hospitalized Elderly Patients Is Not Associated With Excess Mortality. Issue 10 (4th June 2015) - Weiss, Avraham; Grossman, Alon; Beloosesky, Yichayaou; Koren‐Morag, Nira; Green, Hefziba; Grossman, Ehud
<x xml:space="preserve">Abstract</x> Inter‐arm blood pressure difference (IAD) has been found to be associated with cardiovascular mortality. Its clinical significance and association with mortality in the elderly is not well defined. This study evaluated the association of IAD with mortality in a cohort of hospitalized elderly individuals. Blood pressure (BP) was measured simultaneously in both arms in elderly individuals (older than 65 years) hospitalized in a geriatric ward from October 2012 to July 2014. During the study period, 445 patients, mostly women (54.8%) with a mean age of 85±5 years, were recruited. Systolic and diastolic IAD were >10 mm Hg in 102 (22.9%) and 76 (17.1%) patients, respectively. Patients were followed for an average of 342±201 days. During follow‐up, 102 patients (22.9%) died. Mortality was not associated with systolic or diastolic IAD. It is therefore questionable whether BP should be routinely measured in both arms in the elderly.